The Relationship Between Learning Outcomes Of Pastry And Bakery Courses With Students Entrepreneurial Interest Of Family Welfare Education Study Program - Zalukhu, Yulisia; Yulastri, Asmar (Universitas Negeri Padang, 2023)
The background of this research is motivated by the high number of educated unemployment in Indonesia. This study aim to describe: 1) learning outcomes of pastry courses, 2) learning outcomes of bakery courses, 3) student entrepreneurial interest, 4) analyze the relationship between learning outcomes of pastry courses and entrepreneurial interest of family welfare education study program students majoring in culinary arts, 5) analyze the relationship between learning outcomes of bakery courses and entrepreneurial interest of family welfare education study program students majoring in culinary arts, 6) analyze the relationship between learning outcomes of pastry and bakery courses with entrepreneurial interest of family welfare education study program students majoring in culinary arts. This type of research is quantitative with a correlational approach. The research population was 196 students of family welfare education study program majoring in culinary arts class of 2018 and 2019. The sample is 66 people taken by Proportionate Random Sampling. The primary data collection technique uses a questionnaire distributed is measured using a likert scale. Then for secondary data using learning outcomes in pastry and bakery courses. The analysys requirement test was carried out with normality test and linearity test, then test the hypothesis using pearson product moment and multiple correlation coefficient analysis, and then test the significance of the correlation with the t test using help of SPSS 24.00 version. The results showed that: 1) learning outcomes of pastry courses students is in the excellent category (34,8%), 2) learning outcomes of bakery courses students is in the very good category (51,5%), 3) entrepreneurial interest students is in the medium category as many as 37 students, 4) there was a positive and significant relationship between learning outcomes of pastry courses and entrepreneurial interest of family welfare education study program students majoring in culinary arts with a correlation value of rxy0,621 means that it has a strong level of relationship, 5) there was a positive and significant relationship between learning outcomes of bakery courses and entrepreneurial interest of family welfare education study program students majoring in culinary arts with a correlation value of rxy 0,701 means that it has a strong level of relationship, 6)there was a positive and significant relationship between learning outcomes of pastry and bakery courses with entrepreneurial interest of family welfare education study program students majoring in culinary arts with a correlation value of 0,000 < 0,005.